2023
DOI: 10.1021/acs.chemrestox.2c00379
|View full text |Cite
|
Sign up to set email alerts
|

Transparency in Modeling through Careful Application of OECD’s QSAR/QSPR Principles via a Curated Water Solubility Data Set

Abstract: The need for careful assembly, training, and validation of quantitative structure−activity/property models (QSAR/QSPR) is more significant than ever as data sets become larger and sophisticated machine learning tools become increasingly ubiquitous and accessible to the scientific community. Regulatory agencies such as the United States Environmental Protection Agency must carefully scrutinize each aspect of a resulting QSAR/QSPR model to determine its potential use in environmental exposure and hazard assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…Our study corroborates the findings of Lowe et al . 29 , emphasizing the complexity and challenges in solubility prediction across diverse chemical spaces. We found that RF models provide a balanced and interpretable framework.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study corroborates the findings of Lowe et al . 29 , emphasizing the complexity and challenges in solubility prediction across diverse chemical spaces. We found that RF models provide a balanced and interpretable framework.…”
Section: Discussionmentioning
confidence: 99%
“… 28 , and Lowe et al . 29 . In comparison, AqSolDB which was published in 2020 has already been used in 2021 by Francoeur et al .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The tasks and problems spanned by the proposed methods are also highly diverse and range from classical quantitative structure–activity/property relationship (QSAR/QSPR) problems, such as the prediction of drug-induced liver injury (DILI), , Ames mutagenicity, , or acetylcholinesterase (AChE) inhibition, to categorization of chemicals, generating transcriptomic profiles and classifying parts of regulatory documents . In their paper, “Transparency in Modeling through Careful Application of OECD’s QSAR/QSPR Principles via a Curated Water Solubility Data Set”, the authors revisited the five Organisation for Economic Co-operation and Development (OECD) principles for QSAR models. The discussion of these principles, which is ongoing also within OECD, is addressed here with particular emphasis on the case of machine learning (ML) models.…”
Section: Approached Problems and Tasksmentioning
confidence: 99%